Uji aktivitas antibakteri ekstrak etanol daun sungkai (Peronema canescens Jack) terhadap pertumbuhan Escherichia coli dengan metode difusi cakram Kirby-Bauer - Desta Fransisca; Donna Novina Kahanjak; A Frethernety (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2020)
Diarrhea is a serious and dangerous condition that could be caused by Escherichia coli. Sungkai is a plant that easily could be found in Indonesia, especially in Central Borneo. The young leaf of sungkai usually used as traditional medicine and potentially as an antibacterial. Aim of this study was to determine the antibacterial activity from the ethanol extract of sungkai (Peronema canescens Jack) leaf to inhibit the growth of E. coli, examined by Kirby-Bauer’s disc method. Post-test only control group design was the method used in this study. The ethanol extract of sungkai (P. canescens) leaf was tested with various concentration (25%, 50%, 75% and 100%). The results showed that the E. coli’s growth could be inhibited by ethanol extract of sungkai (P. canescens) leaf with a concentration of 25%, 50%, 75% and 100%, proved by 3,75 mm, 3,5 mm, 3,5 mm and 7,75 mm inhibition zone in each of concentration sequentially, with the effective concentration of 25%. It is concluded that the ethanol extract of sungkai (P. canescens) leaf could inhibit the growth of E. coli. Further research should be developed to determine the minimum levels needed to obtain the antibacterial activity of sungkai extract.